Trends and Patterns of Hepatocellular Carcinoma Treatment in Korea - Hong, Young Mi (J Korean Med Sci, 2016)
Multiple therapeutic modalities are available for hepatocellular carcinoma (HCC) treatment. We aimed to evaluate the trends for HCC treatment in Korea. Recent trends and patterns in treatment modalities were assessed in HCC patients who first registered for the Health Insurance Review Assessment Service between 2008 and 2012. From 2009 to 2012, 57,690 patients were diagnosed with HCC. Transcatheter arterial chemoembolization (TACE) was the most common treatment modality for initial treatment. Curative treatment modalities like hepatic resection, liver transplantation, and local ablation therapy increased gradually. The 3 most common treatment modalities (hepatic resection, local ablation therapy, TACE) used after initial treatment in 2009 were studied. Following initial hepatic resection, 44.5% of patients required re-treatment. TACE was the most common modality (in 48.3% of cases), while 15.0% of patients received local ablation therapy. After local ablation therapy, 55.4% of patients were re-treated, wherein 45.0% of patients received TACE and 31.5% received local ablation therapy. Following initial TACE, 73.9% patients were re-treated, most commonly with TACE (57.7%) followed by local ablation therapy (12.8%). While there were no significant differences between the initial and re-treatment modalities, various multiple treatments followed the initial treatment. The treatment modalities were interchangeable.